Teaching Financial Literacy With Max and Ruby. Issue 1 (2nd January 2017) - Brown, Natalya; Ferguson, Kristen
Abstract : Teaching financial literacy is important at all stages of life, but is often neglected with elementary students. In this article, the authors describe a strategy for teaching financial literacy using the books about Max and Ruby by Rosemary Wells. These books can help introduce the five key concepts of financial literacy: scarcity, exchange, money, saving, and giving. The practical and hands-on classroom activities they propose integrate the stories, language arts, and financial literacy through dramatic retelling, using graphic organizers, a learning center, writing and drawing activities, and classroom conversations.